Hybrid and Blended Learning. Issue 2 (September 2015) - O'Byrne, W. Ian; Pytash, Kristine E.
Abstract Hybrid or blended learning is defined as a pedagogical approach that includes a combination of face‐to‐face instruction with computer‐mediated instruction. The terms blended learning, hybrid learning, and mixed‐mode learning are used interchangeably in current research; however, in the United States, hybrid learning is used most often. Although hybrid learning can be diverse in how it is implemented, educators agree that this approach has the opportunity to provide personalized instruction with some element of student control over path, pace, time, and place. Educators and students need to be given the latitude to teach and learn in these hybrid spaces while being protected and supported by schools. Ultimately, teachers and students bear an equal responsibility as they collaboratively learn and experiment in these evolving spaces.